An Active Amorphous Carbon Material with Fe2C Nanocrystals Encapsulated as a High Performance Electrode for Lithium‐Ion Batteries. Issue 5 (17th February 2017) - Che, Haiying; He, Yu‐Shi; Liao, Xiao‐Zhen; Zhang, Hui‐Juan; Zhang, Weimin; Ma, Zi‐Feng
Abstract: A nitrogen and sulfur dual doped carbon with Fe2 C nanocrystals encapsulated material (Fe2 C@C) was synthesized by a simultaneous polymerization‐precipitation technique followed with a high temperature pyrolysis process. This method can lead to an effective and homogenous distribution of core/shell Fe2 C /carbon nanoparticles into the carbon matrix. The optimized material was applied as an anode for a lithium‐ion battery, which showed a high capacity, excellent rate performance, and good cycling capability. It delivered a high specific capacity of 657.7 mA h g −1 at a current density of 0.2 A g −1, and even at a very high current density of 6 A g −1, the electrode still retained a very high specific capacity of 509.1 mA h g −1 . After 150 cycles of charge/discharge at a current density of 1 A g −1, no capacity decay was observed which presents itself a promising high performance anode for LIBs. It may be ascribed to that the presence of Fe2 C can greatly stabilize the structure of the electrode and the electrode process for the lithiation/delithiation of LIBs. Abstract : A nitrogen and sulfur dual doped carbon with Fe2 C nanocrystals encapsulated material (Fe2 C@C) was synthesized via a simultaneous polymerization‐precipitation method followed with a subsequent high temperature pyrolysis process. This carbides/carbon structure deliveries a very high capacity and exhibits a superior rate performance as an anode for lithium‐ion battery.